Pengendalian Kualitas Labelling pada Botol Oli Menggunakan Metode DMAIC di PT Bumimulia Indah Lestari - Rahmat Tri Basuki; Uly Amrina (Engineering Faculty at Universitas Singaperbangsa Karawang, 2022)
PT Bumimulia Indah Lestari found defects in the oil bottle packaging products it produces, which include perforated bottles, black spots on bottles, and defects on labels. The type of defect on the bottle label is the highest defect in the period from July to December 2021 compared to other defects. This research is focused on the problem of defects in the inverted label as the dominant defect of the entire defect label. Researchers use the DMAIC method to solve these problems. The improvement resulting from the DMAIC method is the manufacture of a jig tool called Jig Go No Go which aims to reduce the number of defects and increase productivity in bottle products. The implementation of the jig can reduce the defect label as a whole from 5.8% to 3.3% and the sigma value increases from 2.488 to 2.493.